(untitled) (Journal of the College of Basic Education, 2023)
The history of Afghanistan in the nineteenth century and the beginning of the following century witnessed colonial competition between the major powers at the time; Britain, Russia and some local powers such as Iran, which represents part of its great struggle over colonies and spheres of influence.And because Afghanistan enjoys an important geographical and strategic location, it occupied a prominent position in the British defense plan, which aimed to form a coherent barrier from the regions close to India, the jewel of the British crown, that would be difficult for Russia and others to penetrate. From here, this study traced the course of British relations with Afghanistan, and Britain’s attempts to maintain the Afghan barrier by ensuring its superiority over the rest of its competitors. For this reason, it entered the arena of internal Afghan events during the decades of the nineteenth century, and this intervention varied between military action and diplomatic action to seek to bring Afghanistan into its ranks in its conflict with Russia, whose expansionist policy in northern Afghanistan posed a serious challenge to British interests, taking advantage of the difficult conditions of Afghanistan. To extend its influence to it to be close to the British possessions in India, and to encourage the Iranian rulers to occupy the Afghan emirates.